Financial Performance Analysis of PT Senantias Makmur - Cahyani, Binda Rahma; Sudirman, Wahyu Febri Ramadhan; Reza, Saru (Journal of Financial and Business, 2024)
Financial ratio analysis is an important tool for evaluating a company's financial performance, identifying trends, and determining existing financial strengths and weaknesses. This study analyzes PT Senantiasa Makmur's financial ratios for 2022 and 2023, including liquidity, solvency and profitability ratios. The analysis results show an increase in the current ratio from 1.6 to 1.8, quick ratio from 1.0 to 1.2, and cash ratio from 0.4 to 0.5, which indicates an improvement in the company's liquidity. In addition, the decrease in Debt to Asset Ratio from 0.63 to 0.60 and Debt to Equity Ratio from 1.70 to 1.50 indicates that the company has reduced its dependence on debt, reducing financial risk. The increase in Return on Assets (ROA) from 0.08 to 0.09 and Return on Equity (ROE) from 0.21 to 0.22 shows that the company is more efficient in using assets and equity to generate profits. Overall, PT Senantiasa Makmur demonstrated significant improvements in financial performance, placing it in a stronger position for future growth and sustainability.